2017
DOI: 10.1589/jpts.29.2085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mirror therapy and electrical stimulation on upper extremity function in stroke with hemiplegic patient: a pilot study

Abstract: [Purpose] This study investigated the effects of mirror therapy and neuromuscular electrical stimulation on upper extremity function in stroke patients. [Subjects and Methods] This study recruited 8 stroke patients. All patients were treated with mirror therapy and neuromuscular electrical stimulation five times per week for 4 weeks. Upper limb function evaluation was performed using upper extremity part of fugl meyer assessment. [Results] Before and after intervention, fugl meyer assessment showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Paik et al reported significant differences in FMA scores in patients with stroke when MT and electrical stimulation were combined. [ 36 ] Jung et al [ 37 ] also reported significant differences in both experimental and control groups before and after MT combined with EMG-triggered FES. Kojima et al [ 38 ] reported the greatest improvement in wrist items when evaluating the FMA after using the ETMS-MT.…”
Section: Discussionmentioning
confidence: 99%
“…Paik et al reported significant differences in FMA scores in patients with stroke when MT and electrical stimulation were combined. [ 36 ] Jung et al [ 37 ] also reported significant differences in both experimental and control groups before and after MT combined with EMG-triggered FES. Kojima et al [ 38 ] reported the greatest improvement in wrist items when evaluating the FMA after using the ETMS-MT.…”
Section: Discussionmentioning
confidence: 99%
“…Although this corresponds to the study by Yoon et al [46], which reveals significant differences in Box and Block Test results for constraint-induced therapy for stroke patients, and the study by Dos et al [47], which reveals significant differences in Jebsen-Taylor Hand Function Test results for peripheral nerve stimulation training for stroke patients. Paik et al [48] reported significant improvements in the Fugle-meyer assessment, applying the training of mirror therapy and electrical stimulation to stroke patients.Exercising only the damaged joints of stroke patients creates a high level of inhibitory activity between hemispheres which is aimed at the motor cortex within the damaged cerebral hemisphere. However, bilateral simultaneous use balances the level of interaction between hemispheres and tends to normalize the level of inhibitory activity, thus greatly benefiting motor control [49].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke survivors often have varying degrees of motor function impairment, especially in the upper extremities, which can lead to long-term disability and poor quality of life. 1 Several methods have been proposed for the rehabilitation of hemiplegic upper extremities; [2][3][4] however, it remains the most common deficit following a stroke.…”
Section: Introductionmentioning
confidence: 99%